Students' strategies for learning identities as industrial workers in a Swedish upper secondary school VET programme - Ferm, Lisa [Verfasser]; Persson Thunqvist, Daniel [Verfasser]; Svensson, Louise [Verfasser]; Gustavsson, Maria [Verfasser] (My University, 2018)
"The aim of this article is to investigate the learning strategies vocational students use to become part of a work community, and how these strategies are related to the formation of a vocational identity at the workplace. Conducting qualitative interviews, data were collected from 44 industrial programme students from six upper secondary schools. The findings revealed five recurrent strategies used by the students for learning vocational identities as industrial workers. The students took individual responsibility for their own learning, asked questions to gain deeper vocational knowledge, searched for role models in the work community, positioned themselves as a resource to the work community, understood and used humour and jokes in order to become a member of the community. The conclusion is that the students actively develop learning strategies to adapt their behaviour to the norms and ideals of the industrial work community. In the process of develop the vocational identities as industrial workers, the students’ vocational habitus is transformed to better fit the industrial work community. The integration of the notions of agency and habitus demonstrates the dynamic nature of students' participation in work communities; simultaneously, the students reproduce social structures that promote vocational identities." (Author's abstract ; BIBB-Doku)
Keywords: G 2.4.4 Biografiegestaltung; S 6.2 Fertigungsberufe; P 2.3 Auszubildende; I 2.2.1 Westeuropa; Berufliche Identität; Industrieberuf; Industriearbeiter; Lernstrategie; Berufsschüler; Schweden